2021
DOI: 10.4310/hha.2021.v23.n1.a8
|View full text |Cite
|
Sign up to set email alerts
|

Unstable algebras over an operad

Abstract: The aim of this article is to define and study a notion of unstable algebra over an operad that generalises the classical notion of unstable algebra over the Steenrod algebra. For this study we focus on the case of characteristic 2. We define ⋆unstable P-algebras, where P is an operad and ⋆ is a commutative binary operation in P. We then build a functor that takes an unstable module M to the free ⋆-unstable P-algebra generated by M . Under some hypotheses on ⋆ and on M , we identify this unstable algebra as a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Both the Brown-Gitler and the Carlsson modules are endowed with a multiplication which naturally arises when studying their structure. It has been shown that certain of these modules, with their respective multiplication, are in fact free objects in a specified category of (non-associative) algebra [11,17].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Both the Brown-Gitler and the Carlsson modules are endowed with a multiplication which naturally arises when studying their structure. It has been shown that certain of these modules, with their respective multiplication, are in fact free objects in a specified category of (non-associative) algebra [11,17].…”
mentioning
confidence: 99%
“…In [17], we introduced a notion of unstable algebra over an operad in characteristic two. For an operad P and a commutative operation ⋆ ∈ P(2), a ⋆-unstable P-algebra is an unstable module A over the mod 2 Steenrod algebra, endowed with an action of P, satisfying the following identity, called instability:…”
mentioning
confidence: 99%
See 3 more Smart Citations